2013
DOI: 10.1371/journal.pone.0055769
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Transcriptome Profiling of Lithium Stimulated Human Mesenchymal Stem Cells Reveals Priming towards Osteoblastic Lineage

Abstract: Human mesenchymal stem cells (hMSCs) present in the bone marrow are the precursors of osteoblasts, chondrocytes and adipocytes, and hold tremendous potential for osteoregenerative therapy. However, achieving directed differentiation into osteoblasts has been a major concern. The use of lithium for enhancing osteogenic differentiation has been documented in animal models but its effect in humans is not clear. We, therefore, performed high throughput transcriptome analysis of lithium-treated hMSCs to identify al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 90 publications
(103 reference statements)
7
46
1
Order By: Relevance
“…Some studies suggest that lithium causes bone loss that can predispose or aggravate osteoporosis [171,172], whereas other studies did not find any significant effects [173]. In contrast, several studies highlighted beneficial effects of lithium on bone metabolism, including inhibition of bone resorption and osteoclast formation, possibly via modulation of the canonical Wnt/␤-catenin pathway [174][175][176][177][178].…”
Section: Lithiummentioning
confidence: 99%
“…Some studies suggest that lithium causes bone loss that can predispose or aggravate osteoporosis [171,172], whereas other studies did not find any significant effects [173]. In contrast, several studies highlighted beneficial effects of lithium on bone metabolism, including inhibition of bone resorption and osteoclast formation, possibly via modulation of the canonical Wnt/␤-catenin pathway [174][175][176][177][178].…”
Section: Lithiummentioning
confidence: 99%
“…MSC differentiation has been a focus of past comparative transcriptome approaches, which has included studies of functional differences in MSC populations (Jansen et al, 2010), characterization of MSC stemness (Gao et al, 2013;Steinert et al, 2015), and assessments of differentiation status (Brown et al, 2015;Granchi et al, 2010;Liu et al, 2014;Menssen et al, 2011;Modder et al, 2012;Satija et al, 2013;Skreti et al, 2014;Steinert et al, 2015;Wislet-Gendebien et al, 2012;Yu et al, 2013;Zhang et al, 2014). For example, temporal and spatial patterns of gene expression profiles were reported for chondrogenic differentiation (Skreti et al, 2014).…”
Section: Tracking Cell Differentiationmentioning
confidence: 99%
“…Activation of this pathway through cell exposure to Li has been reported to promote osteoblastogenesis and inhibit osteoclastogenesis, leading to an increase in bone formation and volume in rats [13,14]. The effects of lithium on bone density have been investigated, with some authors observing that it might interfere with calcium transport within the body [15], enhance the proliferation, differentiation and cementogenic gene expression in human periodontal ligament-derived cells [16] and osteogenic differentiation in mesenchymal stem cells (MSCs) [17]. A study investigating the effects of lithium in patients treated with lithium carbonate found that such treatment may enhance or preserve bone mass [18].…”
Section: Introductionmentioning
confidence: 99%